MODERN APPROACHES TO THE THERAPY OF VIRAL PAPILLOMA SKIN INFECTION IN INFANCY - L.K. Aslamazian; L.S. Namazova; L.P. Mazitova (Вопросы современной педиатрии)
To improve the methods of prevention and treatment of viral papilloma infection, the researchers examined 80 children, suffering from skin forms of a disease. They examined peculiarities of a disease and interferon status of all the children. The data of clinic and laboratory research allowed them to assume that viral papilloma infection grows along with the reduction of immune mechanisms and it grows among the children, suffering from the genetic burden to viral diseases. All the patients, suffering from the disorder of interferon status, have undergone the complex therapy, which included medications of recombinant interferon (Viferon) in suppositories and extrinsic. For the first time, the researchers removed the skin papillomas by a combination method: cryofreezing and photovaporization. The analysis of treatment and observation within a year and a half showed that in a group of children, who received a combination treatment, including Viferon therapy and removal of verrucas by 2 surgical methods. No backset of a disease detected. In general, the findings of the research pointed out the high efficiency of topical and systemic Viferon medications, as well as combination method of verruca removal in complex treatment of viral papilloma skin infection among the children.Key words: interferon status of children, interferon al'fa 2b, verrucas, viral papilloma infection.